ADAPTACION DEL DISCURSO DEL PROFESOR DE L2 A LA COMPETENCIA TRANSICIONAL DEL ALUMNO DE NIVEL ELEMENTAL - Fonseca Mora, Carmen; Cuenca Villarín, María Heliodora (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Studies about interaction between speakers with more linguistic and communicative competence and speakers who have not yet fully developed their abilities of expression describe a series of modifications in the higher level speaker’s speech in order to facilitate communication between them. We will go through the literature to detail the described modifications and establish a parallelism between L1 and L2 adult speech features when they act as linguistic models. We will demonstrate the existence of such adaptations in the speech of a random selection teachers who teach English to Spanish students at the beginning level and describe the students’ poor development of understanding and oral expression skills in the Spanish educational system.